Intestinal microbial dysbiosis under nitrite stress in juvenile three-keeled pond turtles, Mauremys reevesii - Huo-Bin Tang; Yu-Xin Si; Hua-Dong Li; Wei Dang; Hong-Liang Lu (BMC Microbiology)
Abstract Background Nitrite is one of the primary pollutants in high-density aquaculture systems, and may cause various toxic effects (e.g., oxidative damage, metabolic and immune dysregulation, histological inflammation, etc.) on economically important aquaculture species, such as echinoderms, crustaceans and fish. Nitrite can also disrupt the intestinal function and microbiota in some fish and amphibians. However, intestinal physiological and microbial responses of cultured turtles under nitrite stress were rarely explored. Method Twenty Mauremys reevesii juveniles were exposed to different nitrite levels and fed with a commercial diet. Their intestinal content samples were analyzed for microbial diversity and composition. Results Nitrite exposure reduced intestinal microbial diversity, with lower α-diversity values in higher-concentration exposed turtles. It also changed the microbial composition. After exposure, the abundances of Bacteroidetes and Firmicutes decreased, but that of Proteobacteria increased at the phylum level. Similarly, abundances of some potentially beneficial bacterial genera, e.g., Prevotella_1, Christensenellaceae_R-7, Muribaculaceae_ge, were shown to decrease, but those of putatively pathogenic genera, e.g., Halomonas, Nesterenkonia, increased at the genus level. Furtherly, potentially altered metabolic pathways (e.g., biosynthesis of ansamycins and vancomycin group antibiotics) were revealed by functional predictions of intestinal microbiota. Conclusion This study highlighted intestinal microbial dysbiosis and prevalence of putatively pathogenic bacteria in cultured turtles under nitrite stress. Excessive levels of nitrite would alter the health status of aquatic animals by disrupting their intestinal microbiome.